STUDY OF SURFACE MOVEMENTS OF OIL AND GAS FIELDS - М.Ш. Ўролова; Н.М. Муҳаммадқулов; Б.Б. Хайриддинов (Journal of new century innovations, 2023)
This article examines surface displacements observed in oil and gas fields. The factors affecting the surface displacement observed in the mines were studied. In order to study the relationship between the identified factors, correlational and regression relationships are analyzed. These analyzes were conducted using MS Excel.